2017
DOI: 10.5194/essd-9-791-2017
|View full text |Cite
|
Sign up to set email alerts
|

A global satellite environmental data record derived from AMSR-E and AMSR2 microwave Earth observations

Abstract: Abstract. Spaceborne microwave remote sensing is widely used to monitor global environmental changes for understanding hydrological, ecological, and climate processes. A new global land parameter data record (LPDR) was generated using similar calibrated, multifrequency brightness temperature (T b ) retrievals from the Advanced Microwave Scanning Radiometer for EOS (AMSR-E) and the Advanced Microwave Scanning Radiometer 2 (AMSR2). The resulting LPDR provides a long-term (June 2002-December 2015 global record of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 69 publications
3
146
0
1
Order By: Relevance
“…Surface air temperature and RH measurements from in situ weather stations were used to represent variations in seasonal climate for the different snow conditions in this study even though the AMSR FT retrieval is more directly sensitive to land surface dielectric changes due to FT related shifts in liquid water abundance (Du et al 2017). Alternatively, surface 'skin' temperatures from the MODIS (MYD11A1) land surface temperature (LST) record were analyzed for the same domain, period and snow (SCE) conditions (figure S4); the LST retrievals are a closer proxy of the energy state within the surface snow layer represented by the AMSR FT retrieval, while the LST results were consistent with the in situ air temperature assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Surface air temperature and RH measurements from in situ weather stations were used to represent variations in seasonal climate for the different snow conditions in this study even though the AMSR FT retrieval is more directly sensitive to land surface dielectric changes due to FT related shifts in liquid water abundance (Du et al 2017). Alternatively, surface 'skin' temperatures from the MODIS (MYD11A1) land surface temperature (LST) record were analyzed for the same domain, period and snow (SCE) conditions (figure S4); the LST retrievals are a closer proxy of the energy state within the surface snow layer represented by the AMSR FT retrieval, while the LST results were consistent with the in situ air temperature assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The AMSR orbital swath T data were spatially resampled to a 6 km resolution polar EASE-Grid (version 2) geographic projection, using an inverse distance squared weighting method (Brodzik et al 2012, Du et al 2017a. To ensure cross-sensor consistency, the gridded AMSR2 T data were empirically calibrated against the same AMSR-E frequencies using a double-differencing method and similar overlapping observations from the FY3B MWRI sensor record (Du et al 2017b, Du et al 2014. The new 6 km grid provided an intermediate resolution between the finer scale (500 m) MODIS SCE and the coarser resolution (∼12.5 km) AMSR T observations, while enabling enhanced assessment of terrain and land cover spatial heterogeneity.…”
Section: Spatially Resampled Amsrmentioning
confidence: 99%
“…We use the descending orbit as retrievals are generally more accurate when vertical temperature gradients are low (Liu et al, 2011). The retrieval specifically accounts for the effects of open water on the VOD and surface-soil moisture (Du et al, 2017b). The accompanying quality flags are used to remove all pixel values observed under non-favourable conditions with respect to frozen soils, snow, ice or large areas of open water on the surface, very dense vegetation, precipitation, radio frequency interference, or microwave signal saturation.…”
Section: Vegetation Optical Depth and Land Surface Parametersmentioning
confidence: 99%
“…Accordingly, changes in species composition (Chapin et al, 1995) are observed and satellite records indicate a greening in large regions in the Arctic Verbyla, 2008). This is interpreted as increased growth (Stow et al, 2004;Elmendorf et al, 2012;Huemmrich et al, 2010a;Chapin et al, 1995) or even as a woody encroachment into tundra (Racine et al in Stow et al, 2004;Dass et al, 2016;Sturm et al, 2001). Yet, higher leaf mass and growth do not necessarily linearly translate into enhanced GPP in every case, as increased growth might also cause enhanced self-shading and lower nitrogen amounts per unit leaf area (Street et al, 2007;McFadden et al, 2003).…”
mentioning
confidence: 99%